The Risks of Obesity, Weight Control Behaviors, and Disordered Eating to Adolescents - Emily Johnson; Kate Fogarty (EDIS)
Over the past 15 years, unhealthy weight-loss behaviors among U.S. adolescents are becoming more widespread. This 5-page fact sheet addresses the consequences and risks associated with risky weight-control practices and discusses the prevalence of eating disorders and the role of body image in weight practices. The publication also provides references that can be used to help practitioners educate youth on the importance of setting realistic goals and enhancing body satisfaction. Written by Emily Johnson and Kate Fogarty, and published by the UF Department of Family, Youth and Community Sciences, September 2014. (AP Photo/University of Florida/IFAS/Josh Wickham)